Konstruksi Makna dan Sentimen: Representasi Dunia Pertanian dalam Platform YouTube di Indonesia - Muhammad Umaruddin; Ahmad Febriansyah; Nabila Tahira (Society, 2025)
This study examines how the farming profession is portrayed and understood on YouTube, a platform that has received little attention in previous academic work. Drawing on Stuart Hall’s theory of representation and using a digital ethnography approach, the research analyzes six selected YouTube videos, identified through the PRISMA method. Through thematic analysis using ATLAS.ti, the study identifies key symbolic representations, while sentiment analysis with AI Studio categorizes audience responses as positive, negative, or neutral. The findings suggest that video formats—such as monologues, vlog-style storytelling, and complex editing—contribute to diverse portrayals of farmers. Negative portrayals, as seen in Indonesia Terancam Krisis Petani Muda (CNN Indonesia), tend to reinforce views of farming as difficult and economically insecure. On the other hand, videos like Pengantin Baru Lulusan Sarjana Sukses Jadi Petani (Wong Ladangan) offer more positive narratives, showing farming as a viable and rewarding profession. This study contributes to discussions on digital representation by showing how online media shape public perceptions of professional identities. It also provides practical insights for agricultural policymakers and content creators to rethink how farming is communicated to the public, particularly to younger audiences.